Il nomadismo tra lingue e culture raccontato da Cristina Ali Farah nel romanzo Madre piccola - Chmiel, Aneta (Romanica Silesiana)
The present article offers an analysis of Cristina Ali Farah’s novel, Madre piccola. Even though it is generally believed that postcolonial novels have only been written in English, Farah’s book can definitely be classified as such, as it examines the specificity of the Italian post-colonial period, as well as the situation of women and other minority groups. Madre piccola portrays the lives of four women living on the border of two cultures. The nomadic society presented in the text-marked by temporariness, moving from one place to another-is not perceived as “local” anymore, but is presented in a more global context. The title Madre piccola means “mother’s aunt” in the Somalian language, and is an example of a word-for-word translation. Importantly, the world of women and immigrants as depicted by Farah has not been known in Europe so far. That world is far more emancipated and modern than one could expect. Ali Farah’s writing tackles not only the nature-and preservation-of what is local, but also the development of the global culture. Key words: Post-colonial Italian women’s literature, immigrants, nomadic society.